Notary Compliance with Money Laundering Crime Rules in Business Transactions - Yanti, Fitra Gusma (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Notary Compliance with Money Laundering (TPPU) is a transnational crime that threatens the stability of the global financial system. Notaries, as Public Officials authorized to make authentic deeds, have a strategic role in helping to prevent Money Laundering. This study aims to analyze the obligation of notary compliance with the rules of money laundering in suspicious business transactions and the reporting process. The approach to this research uses the normative juridical approach method and descriptive analysis research specifications. The data used are secondary data with data collection methods using literature studies. Secondary data used in this study include primary legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials consist of laws and regulations related to the research being carried out. Secondary legal materials consist of books, journals. While tertiary legal materials are encyclopedias, magazines, newspapers, articles. The results of the study and discussion show that the obligation of notary compliance with Money Laundering Crimes (TPPU) in business transactions, the first is that notaries are required to report suspicious business transactions because it can make it easier for PPATK to prevent and eradicate money laundering by utilizing several roles of Notaries as Public Officials and Professionals who are interrelated in digging up data on Service Users. And the second is the process of reporting suspicious financial transactions by Notaries with several steps. First, Notaries appoint reporting officers who are responsible for monitoring and identifying suspicious transactions. Second, Notaries must register through the GoAML application. Third, Notaries are required to report suspicious transactions to PPATKap Money Laundering Crime Rules in Business Transactions